Extended Hermite-Hadamard (H − H) and Fejer’s Inequalities Based on (H1, H2, S)-Convex Functions - Yasin, Sabir; Misiran, Masnita; Omar, Zurni (Etamaths Publishing, 2022)
In this paper, (h1, h2)-convex and s-convex functions are merged to form (h1, h2, s)-convex function. Inequalities of the Hermite-Hadamard (H-H) and Fejer’s types will then be extended by using the (h1, h2, s)-convex function and its derivatives. Some special cases for these extended H-H and Fejer’s inequalities are also explored in order to get the previously specified results. The relationship between newly constructed Hermite-Hadamard (H − H) and Fejer’s types of inequalities with the average (mean) values are also discussed